Inclusive Growth and Inequality in Senegal - Kireyev, Alexei (IMF Working Papers; Working Paper ;, 2013)
The paper examines Senegal's growth performance from the perspective of its povertyreducing and distributional characteristics, and discusses policies that might help make growth more inclusive. The main findings are that poverty has fallen in the last two decades, but poverty reduction has slowed in recent years. Although available indicators sometimes give conflicting signals on distributional shifts, people in the middle of the income distribution have received the most benefit, mainly in urban areas. Further progress in poverty reduction and inclusiveness would require sustained high growth and exploration of growth opportunities in the sectors with high earning potential for the poor. Better-targeted social policies and more attention to the regional distribution of spending would also help reduce poverty and improve inclusiveness.